Resistance to inhibitors of the human immunodeficiency virus type 1 integration - Daria J. Hazuda, PhD (Brazilian Journal of Infectious Diseases, 2010)
This review will summarize the role of integrase in HIV-1 infection, the mechanism of integrase inhibitors and resistance with an emphasis on raltegravir (RAL), the first integrase inhibitor licensed to treat HIV-1 infection. Keywords: antiretrovirals, integrase inhibitors, raltegravir